2008
DOI: 10.1007/s10812-008-9084-8
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of the POPOP molecule by electron-impact ionization

Abstract: Single and dissociative ionizations of the POPOP molecule by electron impact in the gas phase are studied using mass spectroscopy. Fragmentation pathways of the molecule are proposed taking into account the common system of conjugated π-electrons and heteroatoms in the POPOP molecule. The appearance thresholds for certain fragments of the molecule are determined based on experimentally measured ionization cross sections as functions of the ionizing electron energy. An ion with m/z = 144 [C 9 H 6 ON] + that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The energy dependence of the POPOP molecule single ionization cross-section is measured in the energy range 6-60 eV, from the threshold part of which the first ionization potential for the molecule was determined as E i = 8.74 eV; from the initial parts of the dissociative ionization cross-section plots the appearance threshold energies E ap for [C 6 A characteristic feature of the temperature dependence is the intensity increase with temperature; however, no noticeable increase of the fragmentation depth with temperature is observed that is related to the specific structural features of organic compounds with conjugated bonds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The energy dependence of the POPOP molecule single ionization cross-section is measured in the energy range 6-60 eV, from the threshold part of which the first ionization potential for the molecule was determined as E i = 8.74 eV; from the initial parts of the dissociative ionization cross-section plots the appearance threshold energies E ap for [C 6 A characteristic feature of the temperature dependence is the intensity increase with temperature; however, no noticeable increase of the fragmentation depth with temperature is observed that is related to the specific structural features of organic compounds with conjugated bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectrum of the POPOP molecule is characterized by high selectivity and low fragmentation depth [6]. Fig.…”
Section: Mass Spectrummentioning
confidence: 99%
See 3 more Smart Citations